Evolution and physiology of neural oxygen sensing - Costa, Kauê M.; Accorsi-Mendonça, Daniela; Moraes, Davi J. A.; Machado, Benedito H. (Frontiers in Physiology, 2014)
Major evolutionary trends in animal physiology have been heavily influenced by atmospheric O2 levels. Amongst other important factors, the increase in atmospheric O2 which occurred in the Pre-Cambrian and the development of aerobic respiration beckoned the evolution of animal organ systems that were dedicated to the absorption and transportation of O2, e.g., the respiratory and cardiovascular systems of vertebrates. Global variations of O2 levels in post-Cambrian periods have also been correlated with evolutionary changes in animal physiology, especially cardiorespiratory function. Oxygen transportation systems are, in our view, ultimately controlled by the brain related mechanisms, which senses changes in O2 availability and regulates autonomic and respiratory responses that ensure the survival of the organism in the face of hypoxic challenges. In vertebrates, the major sensorial system for oxygen sensing and responding to hypoxia is the peripheral chemoreflex neuronal pathways, which includes the oxygen chemosensitive glomus cells and several brainstem regions involved in the autonomic regulation to the cardiovascular system and respiratory control. In this review we discuss the concept that regulating O2 homeostasis was one of the primordial roles of the nervous system. We also review the physiology of the peripheral chemoreflex, focusing on the integrative repercussions of chemoreflex activation and the evolutionary importance of this system, which is essential for the survival of complex organisms such as vertebrates. The contribution of hypoxia and peripheral chemoreflex for the development of diseases associated to the cardiovascular and respiratory systems is also discussed in an evolutionary context.